PEMBERDAYAAN KAWASAN PESISIR UTARA BANTEN MELALUI KELOMPOK USAHA BERSAMA BERBASIS KEARIFAN LOKAL - Wigati, Restu; Kulsum, Kulsum; Bethary, Rindu Twidi (Universitas Sultan Ageng Tirtayasa, 2018)
One of the constraints of coastal areas is the difficulty of providing clean water caused by the entry of sea water into the ground water. The difficulty in obtaining clean water makes Domas Village community to find an alternative, one through the use of the rainwater. In addition to clean water problems, poverty is also one of the complicated problems in Pontang Sub-district. The Real Work Experience Community Empowerment Learning (KKN-PPM) conducted by the team of Field Supervisors and Students of the University of Sultan Ageng Tirtayasa (UNTIRTA) by creating and applying a simple water purification equipment design to meet the needs of clean water, improve and develop the business groups of society through its typical food is